Tecnologías de Información y Comunicación: el caso de las comunidades indígenas cabécares de Chirripó de Costa Rica - Brenes-Granados, Cristian (2007)
This article presents a software called "Cosmo vision and mother tongue Cabécar Course", which presents the world vision thorough the mother tongue of Costa Rican Cabecares indigenous communities located in Chirripó. Also shows that information and communication technologies are an opportunity to build a relation that allows intercultural coexistence and recognize the contribution to Costa Rican society of this human group.